Reform in Student Affairs A Critique of Student Development - Bloland, Paul A.; ERIC Clearinghouse on Counseling and Student Services ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
This monograph provides an intensive examination of the student development movement in college student affairs. Chapter I examines student development as a reform movement within the field of student affairs in higher education. Chapter II challenges the assertion that student development as conceptualized in its seminal documents represents a new philosophical foundation and rationale for the field of student affairs. Chapter III raises a number of significant questions regarding current student development theories and the way they have been implemented on the college campus, employing six criteria of effective theory as an assessment template. Chapter IV discusses research on student development, particularly inquiries into the efficacy of student development interventions, and makes a series of observations regarding the research problems noted. Chapter V critiques the non-research literature of student development, looking particularly at journal articles, textbooks, and practitioner-oriented books. Chapter VI discusses the relationship between current student development theory and practice, the contributions of theory, and the problems that the use of student development theory has created for the field of student affairs. Chapter VII concludes the critique by pulling the previous six chapters together and offering a vision of an alternative paradigm for the student affairs field, one that places it firmly within the context of the mission of higher education while avoiding many of the problems noted in the evaluation of the current fledgling paradigm of student development. (NB)
Availability: CAPS, Inc., School of Education, University of North Carolina at Greensboro, Greensboro, NC ($16.95).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: RR93002004.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Students; Educational Change; Higher Education; Student Development; Student Needs; Student Personnel Services; Student Personnel Workers; Guides, Non-Classroom.; ERIC Publications